- ENHANCING COTTON GINNING PROCESSING METHOD FOR BETTER FIBRE QUALITY: COTTON GINNING PROCESSING - Salokhiddinova, Makhliyo; Juraeva, Gulhayo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Cotton, as a fundamental fibre source for the textile industry, plays a pivotal role in global economic development. The quality of cotton fibre is of paramount importance, as it directly influences the final product's characteristics. In this research article, we explore various methods to enhance cotton processing techniques, aiming to produce better-quality cotton fibre.